Agile-Scrum and Business Model Canvas in it Project Management: Integration, Effectiveness, and Critical Success Factors - Systematic Literature Review - Kahpi Baiquni Arifani; Dody Pintarko; Anggraini Puspita Sari (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2026)
A Information systems (IS)/information technology (IT) project management is a critical aspect of successful technology implementation in organizations. Agile and Scrum methodologies have been proven to improve software development effectiveness, while Business Model Canvas (BMC) helps organizations design innovative and sustainable business models. This Systematic Literature Review (SLR) aims to identify, analyze, and synthesize findings from various empirical studies on the application of Agile, Scrum, and Business Model Canvas in IS/IT project management, and explore the integration of these two approaches. This study uses the PRISMA 2020 protocol with an analysis of 95 journals published between 2020 and 2025. Search databases include Google Scholar, SCOPUS, and local institutional repositories. Inclusion criteria include Indonesian/English language studies with a focus on Agile-Scrum (58 journals) and Business Model Canvas (37 journals). The analysis shows that: (1) Agile-Scrum implementation increases development efficiency by 30-50% with a 61.1% (58/95) increase in team adaptability; (2) Business Model Canvas is effective in business strategy with 38.9% (37/95) adoption in empirical studies; (3) Agile-Scrum and BMC integration is found in 15.8% of journals with more positive results (average score 9.3/10 vs 7.2 for Agile-only); (4) Critical Success Factors include organizational leadership (85%), team capability (82%), and stakeholder involvement (75%). The integration of Agile-Scrum with Business Model Canvas results in a holistic approach that combines operational and strategic aspects, increasing the probability of IS/IT project success by up to 78% compared to a single approach. However, implementation still faces challenges related to organizational culture changes, resource availability, and long-term impact evaluation.